Dynamic characterisation of Össur Flex-Run prosthetic feet for a more informed prescription - Noroozi, Siamak; Ong, Zhi Chao; Khoo, Shin Yee; Aslani, Navid; Sewell, Philip (SAGE Publications, 2019)
Background: The current method of prescribing composite running-specific energy-storing-and-returning feet is subjective and is based only on the amputee’s static body weight/mass. Objectives: The aim was to investigate their dynamic characteristics and create a relationship between these dynamic data and the prescription of foot. Study Design: Experimental Assessment. Methods: This article presents the modal analysis results of the full range of Össur Flex-Run ™ running feet that are commercially available (1LO–9LO) using experimental modal analysis technique under a constant mass at 53 kg and boundary condition. Results: It was shown that both the undamped natural frequency and stiffness increase linearly from the lowest to the highest stiffness category of foot which allows for a more informed prescription of foot when tuning to a matched natural frequency. The low damping characteristics determined experimentally that ranged between 1.5% and 2.0% indicates that the feet require less input energy to maintain the steady-state cyclic motion before take-off from the ground. An analysis of the mode shapes also showed a unique design feature of these feet that is hypothesised to enhance their performance. Conclusion: A better understanding of dynamic characteristics of the feet can help tune the feet to the user’s requirements in promoting a better gait performance. Clinical relevance: The dynamic data determined from this study are needed to better inform the amputees in predicting the natural frequency of the foot prescribed. The amputees can intuitively tune the cyclic body rhythm during walking or running to match with the natural frequency. This could eventually promote a better gait performance. © The International Society for Prosthetics and Orthotics 2018.